Advanced Research on the Antioxidant Activity and Mechanism of Polyphenols from Hippophae Species—A Review - Ji, Mingyue; Gong, Xue; Li, Xue; Wang, Congcong; Li, Minhui (Molecules (Basel, Switzerland), 2020)
Oxidation is a normal consequence of metabolism in biological organisms. The result is the formation of detrimental reactive oxygen species (ROS) and reactive nitrogen species (RNS). A large number of studies have shown that polyphenolic compounds have good antioxidant properties. Hippophae species plants have high polyphenolic content and are widely used in food, medicinal, or the cosmetic field. The main polyphenols in Hippophae species are flavonoids, phenolic acids and tannins, which have multiple effects. However, there is a limited number of studies on polyphenols in Hippophae species plants. This review systematically summarizes the polyphenols compounds and antioxidant activity of Hippophae species plants, and it is noteworthy that the main mechanisms of the polyphenols of Hippophae with antioxidant activity have been summarized as follows: regulating enzyme activity, affect the antioxidant reaction of cells, and others. This review provides useful information for the further study and application of Hippophae species polyphenols and their antioxidant activity.